Treatment modality and outcomes among early-stage non-small cell lung cancer patients with COPD: a cohort study - Kang, Noeul (J Thorac Dis, 2020)
BACKGROUND: While there is an increasing number of early-stage non-small cell lung cancer (NSCLC) patients with chronic obstructive pulmonary disease (COPD), there are no specific clinical guidelines for treating them. This study aims to evaluate different treatment modalities and corresponding clinical outcomes among early-stage NSCLC patients with COPD. METHODS: We retrospectively reviewed 692 patients with stage I and II NSCLC and COPD from January 2012 to June 2014. Patients were categorized into four groups according to primary treatment modality: surgery only group (n=442), surgery with adjuvant treatment group (n=157), radiotherapy (RT) group (n=48), and supportive care (SC)-only group (n=45). RESULTS: Overall, mortality rate was the highest in the SC-only group (35.7 deaths per 100 person-years), followed by RT group (21.5 deaths per 100 person-years), surgery with adjuvant treatment group (8.9 deaths per 100 person-years) and surgery only group (7.2 deaths per 100 person-years). The adjusted hazard ratios (HR) for all-cause mortality compared to the surgery only group were 1.18 (95% CI, 0.84–1.67) in surgery with adjuvant treatment group, 1.61 (95% CI, 1.01–2.57) in RT group and 3.23 (95% CI, 1.99–5.23) in SC-only group. CONCLUSIONS: Surgical resection should be considered as the first choice for early-stage NSCLC with COPD. Despite poor lung function or general patient condition, RT rather than SC can be an alternative option if surgery is not feasible. A multi-disciplinary approach and active communication between patients and physicians might be helpful for adequate decision-making regarding treatment for patients with early-stage NSCLC and COPD.